POTENCY OF SESAME OIL AS NTIHYPERCHOLESTEROLEMICAGENT IN RATS FED HIGH-FAT DIET - FAROUK K. EL-BAZ,; ZEINAB A. SALAMA,; HANAN F. ALY,; HANAN A. TAIE, (International Journal of Pharma and Bio Sciences, 2015)
The present study aims to investigate the anti-hypercholesterolemic effects of sesame oil in a high-fat fed rat's model for ninety days. Black sesame oil (BSO) rich in linoleic acid (omega 6 and 9) was tested to evaluate prophylactic, protective and therapeutic hypolipidemic effects in comparison with evening primrose oil (rich in linoleic acid and γ- linolenic acid, omega 6) and with olive oil (rich in oleic acid and omega 9). The serum total lipid (TL), total cholesterol (TC), triglycerides (TG), high density lipoprotein-cholesterol (HDL-C), low density lipoprotein-cholesterol (LDL-C), risk ratio (RR), and liver function enzyme activities; aspartate and alanine aminotransferases (AST and ALT) as well as alkaline phosphatase (ALP) were investigated. Hypercholesterolemic feeding rats resulted in significant elevation of TC, TG, LDL-C, HDL-C, AST and ALT as compared to the rats feeding normal diet (ð‘ƒ< 0.05). Supplementation of hyperlipidemic rats with sesame oil was found to have lower circulating concentrations of TC, LDL-C, HDL-C, AST and ALT (ð‘ƒ< 0.05), and normalized TG level in therapeutic rats supplemented with sesame oil as well as ameliorate serum levels of total lipid and hepatic enzyme activities in rats under a high-fat diet.